Pengembangan Sistem Informasi Manajemen Berbasis Website untuk Meningkatkan Operasional Masjid Al-Mizan - Wibowo, Erlangga Putra; Azizah, Noor; Saputro, Heru (STMIK Banjarbaru, 2025)
Manual mosque management often encounters various challenges, such as data loss, delays in information delivery, and inaccuracies in financial record-keeping, which can hinder operational efficiency. This study aims to develop a web-based Management Information System at Al-Mizan Mosque to address these issues. The system is designed to support mosque administration through key features such as prayer schedule management, coordination of religious activities, financial record-keeping, and management of incoming and outgoing correspondence. The system development follows the Waterfall model, which consists of requirements analysis, system design, implementation, and testing. Blackbox testing results indicate that the system’s features function according to the specified requirements, although certain aspects, such as report generation, still require improvement. Additionally, usability testing using the System Usability Scale produced an average score of 80.1, categorizing the system as suitable for use. This study demonstrates that the developed system can enhance the efficiency of mosque management and improve information accessibility for administrators and congregants.Keywords: Management Information System; Mosque; Waterfall; Blackbox; System Usability Scale. AbstrakPengelolaan masjid secara manual sering menghadapi berbagai kendala, seperti kehilangan data, keterlambatan dalam penyampaian informasi, serta ketidaktepatan dalam pencatatan keuangan, yang berpotensi menghambat efisiensi operasional. Penelitian ini bertujuan untuk mengembangkan Sistem Informasi Manajemen berbasis web di Masjid Al-Mizan guna mengatasi permasalahan tersebut. Sistem ini dirancang untuk mendukung administrasi masjid melalui fitur utama, seperti pengelolaan jadwal ibadah, koordinasi kegiatan keagamaan, pencatatan keuangan, serta pengelolaan surat masuk dan keluar. Pengembangan sistem menerapkan model Waterfall yang terdiri dari tahap analisis kebutuhan, perancangan, implementasi, dan pengujian. Hasil pengujian Blackbox menunjukkan bahwa fitur-fitur sistem berfungsi sesuai dengan spesifikasi yang ditetapkan, meskipun terdapat aspek tertentu, seperti pembuatan laporan, yang masih memerlukan perbaikan. Selain itu, pengujian Usability menggunakan System Usability Scale menghasilkan skor rata-rata 80,1, yang masuk dalam kategori layak digunakan. Penelitian ini menunjukkan bahwa sistem yang dikembangkan dapat meningkatkan efisiensi pengelolaan masjid serta memperbaiki aksesibilitas informasi bagi pengurus dan jamaah.